The Concept Of Relevance In Civil And Economic Procedural Law And Its Relationship With Other Legal Categories - Salimova, Iroda Mamayusufovna (The journal of contemporary issues in business and government, 2021)
This article discusses the concept of relevance in civil and commercial procedural law and analyzes its relationship with such legal categories as competence, jurisdiction and jurisdiction, which are semantically close to each other. The author’s jurisdiction is to determine which public authority or official or non-governmental body (arbitration court, mediator) is authorized by law to consider and resolve claims or other legal issues arising from the legal relationship, and to determine the competence, jurisdiction and judicial institutions. it is concluded that it is an interdisciplinary procedural institution that differs in its legal nature and essence.